Probing calcium solvation by XAS, MD and DFT calculations. Issue 46 (21st July 2020) - Yang, Feipeng; Liu, Yi-Sheng; Feng, Xuefei; Qian, Kun; Kao, Li Cheng; Ha, Yang; Hahn, Nathan T.; Seguin, Trevor J.; Tsige, Mesfin; Yang, Wanli; Zavadil, Kevin R.; Persson, Kristin A.; et al.
Abstract : The solvation shell structures of Ca 2+ in solutions are probed by calcium L-edge soft X-ray XAS and DFT/MD simulations. Abstract : The solvation shell structures of Ca 2+ in aqueous and organic solutions probed by calcium L-edge soft X-ray absorption spectroscopy (XAS) and DFT/MD simulations show the coordination number of Ca 2+ to be negatively correlated with the electrolyte concentration and the steric hindrance of the solvent molecule. In this work, the calcium L-edge soft XAS demonstrates its sensitivity to the surrounding chemical environment. Additionally, the total electron yield (TEY) mode is surface sensitive because the electron penetration depth is limited to a few nanometers. Thus this study shows its implications for future battery studies, especially for probing the electrolyte/electrode interface for electrochemical reactions under in situ /operando conditions.